Epidemiology of Medical Errors and Incidents in Emergency Medicine - Yu. E. Voskanyan (Неотложная медицинская помощь, 2022)
Relevance the issues of patient care and quality management have acquired particular relevance in modern healthcare. Improvement in the clinical performance of medical technologies has led to a significant reduction in deaths and complications associated with the disease and side effects of interventions. As a result, the share of additional harm related to the process of providing medical services has become more noticeable. Accurate data regarding the type, frequency and severity of active threats and incidents they cause are needed to reduce the likelihood and severity of additional harm. In this respect, emergency medical care is the subject of special attention and is characterized by the greatest difficulty in terms of obtaining valid and relevant information about deviations associated with health worker performance, equipment operation and patient behavior.The aim of the study was to explore the main epidemiological characteristics of medical errors and incidents associated with the provision of emergency medical care.Material and methods We present a literature review followed by an analytical study of the epidemiology of incidents and active threats (including medical errors) that precede those incidents in various areas of emergency medical care. By an incident, the authors understood an event with a patient that was more related to the process of providing medical care than to the course of the disease or comorbid conditions which led or could lead to causing additional harm. Active threats included events that subsequently became the direct cause of the incident (medical errors and malpractice, mistakes and deviations in patient behavior, emergency situations in the physical environment). By the “mortality from adverse events”, the authors understood the proportion of deaths from adverse events among all hospitalized patients. By the concept of “lethality associated with adverse events”, the authors denoted the proportion of deaths from adverse events among all the patients affected by adverse events. The search for information was carried out for the period of 1995–2021 using the following medical databases: medline; cochrane collaboration; embase; scopus; isi web of science. For analysis, we used prospective and retrospective observational studies of high methodological quality, meta-analyses and systematic reviews. For the statistical evaluation of frequency characteristics, indicators of incidence, prevalence, and incidence density were used. The calculation of generalized frequency indicators for large samples was carried out with a 95% confidence interval.Results The epidemiology of medical errors and incidents depends on the area in which emergency care is provided. For prehospital emergency medical care, there are 12.45 medical errors and 4.50 incidents with consequences for every 100 visits. In emergency departments, one in fourteen patients suffers additional harm which in 10.14% of cases has severe consequences, and in 3.18% of cases leads to unexpected death. In intensive care units, incidents related to the provision of medical care are recorded in every third patient in the amount of 1.55 per 1 patient. Of these, 58.67% of incidents are accompanied by harm, but the fatality associated with the incidents is only 0.77%. The prevalence of patients affected by incidents during the provision of anesthesia for children is almost 2 times higher than for adults (4.79% vs. 2.03%). At the same time, mortality due to anesthesia-related incidents in children is 11 times lower than in adults (0.27% versus 3.09%). The author draws attention to a number of factors contributing to the development of incidents during the provision of emergency medical care. These include environmental complexity, suboptimal configuration of the workspace, technological interface complexity, the effects of acute stress on performers, and organizational vulnerabilities. A special role was assigned to environmental complexity which was studied in detail both in terms of the complexity of the tasks being solved, and in connection with obstacles to solving problems. It was shown that the intensity of the influence of various components of environmental complexity is not the same in different departments providing emergency care. Particular attention was paid to the fact that organizational vulnerabilities reduce the effectiveness of protective mechanisms during the interaction of the human factor with a complex environment.Conclusion The study showed that the provision of emergency medical care is associated with moderately high risks of incidents, including severe and critical consequences for patients. The main factor contributing to the development of incidents is environmental complexity which becomes much harder to counter under the influence of organizational vulnerabilities. Identification and registration of errors and incidents in units providing medical care is difficult due to the short time of contact with patients, the high speed of situation update, and the constant impact of chronic and acute stressors on staff. In this connection, the optimization and improvement of the efficiency of the system for recording errors and incidents in departments providing emergency medical care remains an area for improvement.